INTERAKSI RESIPROKAL OTAK DAN PERILAKU PADA PERKEMBANGAN ANAK - Santana, Selly Aprilia; Kusumah, Tyara Intana Putri; Purwati, Purwati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The golden period in early childhood is a critical phase in the development of the child's brain, where the neural foundation is intensively formed through experience, social interaction, and parenting patterns. This study aims to examine the reciprocal relationship between brain development and behavior in early childhood and how parenting patterns affect these dynamics. The method used is a literature study with a descriptive qualitative approach, carried out through data collection and secondary data analysis from relevant scientific journal articles. The results of the study indicate that brain function structures such as the prefrontal cortex, amygdala, and hippocampus have an important role in the development of children's behavior and emotional regulation. The development of the prefrontal cortex contributes to the ability to manage emotions, focus attention, and demonstrate children's behavior that is in accordance with social norms. Maladaptive behavior in early childhood that arises due to negative parenting patterns can interfere with and damage the development of brain tissue, especially in the memory and self-control centers, thereby inhibiting healthy brain circuits in children. In conclusion, there is a reciprocal relationship between the brain and children's behavior, where positive, responsive, and consistent parenting plays a major role in shaping healthy neural development in early childhood. This study emphasizes the importance of parenting intervention approaches that support optimal child brain development. ABSTRAKPeriode keemasan pada anak usia dini merupakan fase kritis dalam perkembangan otak anak, di mana fondasi neural dibentuk secara intensif melalui pengalaman, interaksi sosial, dan pola pengasuhan. Penelitian ini bertujuan untuk mengkaji hubungan resiprokal antara perkembangan otak dan perilaku anak usia dini dan bagaimana pola pengasuhan memengaruhi dinamika tersebut. Metode yang digunakan adalah studi literatur dengan pendekatan kualitatif deskriptif, dilakukan melalui pengumpulan data dan análisis data sekunder dari artikel jurnal ilmiah yang relevan. Hasil kajian menunjukkan bahwa struktur fungsi otak seperti prefontal cortex, amigdala, dan hippocampus memiliki peran penting dalam perkembangan perilaku dan regulasi emosi anak. Perkembangan prefontal cortex berkontribusi terhadap kemampuan mengelola emosi, fokus perhatian, serta menunjukkan perilaku anak yang sesuai dengan norma sosial. Perilaku maladaptif anak usia dini yang muncul akibat pola asuh negatif dapat mengganggu dan merusak perkembangan jaringan otak terutama pada pusat memori dan pengendalian diri, sehingga menghambat sirkuit otak anak yang sehat. Kesimpulannya, terdapat hubungan timbal balik antara otak dan perilaku anak, di mana pengasuhan yang positif, responsif, dan konsisten sangat berperan dalam membentuk perkembangan neural yang sehat pada anak usia dini. Penelitian ini menekankan pentingnya intervensi pendekatan pengasuhan yang mendukung perkembangan otak anak secara optimal.